Body, Yoga, and Continuing Teacher Education: experiences and awareness - Rossi, Fernanda [UNESP]; Ehrenberg, Mônica Caldas (FapUNIFESP (SciELO), 2023)
Body, Yoga, and Continuing Teacher Education: experiences and awareness. This study analyzes the potentiality of experiences with yoga in continuing teacher education for the reinterpretation of the corporeality of Kindergarten and Elementary School teachers. This was a qualitative research with 45 teachers of Physical Education, Pedagogy, Art and Special Education, from a city in the interior of São Paulo, with data generated through a focus group and questionnaire. Bodily experiences, as the guiding line of the training process, were shown to contribute to the blurring of the boundaries between what is experienced and what is taught, between the cognitive and the sensitive, enhancing for teachers the expansion of their understanding of themselves and the relationship with the other, in order to reverberate in personal and professional teaching profession.
Corpo, Yoga e Formação Continuada de Professoras: experiências e sensibilizações
Keywords: Basic Education; Body; Continuing Teacher Education; Yoga